Os três problemas clássicos: impossibilidade da solução com régua e compasso e soluções alternativas - Oliveira, Elvis Silva (2017)
This work is about the three classical problems of Greek Geometry: the doubling of the cube, the trisection of the angle and the squaring of the circle. With the aid of some results from the theory of fields we show that such problems can not be solved by the use of only a nongraduated ruler and compass. We present the conchoid, cissoidd and quadratrix curves (also called trissectors) along with their equations. Finally, we present alternative solutions to the three classic problems and highlight how some of the curves previously presented can help such solutions.